2013
DOI: 10.3109/02713683.2013.798667
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Topographic/Tomographic Parameters and Dry Eye Disease in Keratoconus Patients

Abstract: There is no interaction between DES and topographic/tomographic changes in KC-patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
3
18
0
2
Order By: Relevance
“…Moreover, we found TBUT values to be reduced in 73% of KC group patients and, although they were not statistically significant, these results coincide with those of Dogru et al 3 One possible explanation for this is the irregular corneal surface, which would does not permit formation of an adequate tear film. Zemova et al, 35 however, found a relationship between dry eye parameters and corneal irregularity. Additional study is necessary to clarify this point.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, we found TBUT values to be reduced in 73% of KC group patients and, although they were not statistically significant, these results coincide with those of Dogru et al 3 One possible explanation for this is the irregular corneal surface, which would does not permit formation of an adequate tear film. Zemova et al, 35 however, found a relationship between dry eye parameters and corneal irregularity. Additional study is necessary to clarify this point.…”
Section: Discussionmentioning
confidence: 96%
“…Present-day computerized Placido topography systems offer direct digital analysis of the image scene of the Placido mires projected onto the cornea and thus provide a valid and effective tool for detection of corneal irregularities. 1 In addition to axial and tangential curvature maps, 2 several other parameters (eg, corneal surface irregularity indices and Fourier and Zernike aberrations) 3 are available and might increase the sensitivity and specificity when evaluating refractive surgery patients. 4 Detailed topography data are customarily used in surgical planning, 5 especially in topography-guided treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between ocular surface disease and KC stage has also been verified [25]. Although some of the KC screening indices are also sensitive to dry eye syndrome [26], no interaction between measures of dry eye syndrome and topographic/tomographic changes in KC patients could be shown [27].…”
Section: Introductionmentioning
confidence: 89%
“…A total OSDI score, vision-related subscore (derived from questions about vision and task performance), and discomfort-related subscore (derived from questions about ocular surface discomfort) were calculated for each participant as described by Mathews et al [29]. Score ranges were designated as normal (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), or severe (33-100) ocular surface disease.…”
Section: Methodsmentioning
confidence: 99%